Evaluation of Thermal Image Processing and Applications - M. Neethu Sathyan, Dr. K. Sashi Rekha, Dr. G. Victo Sudha George (International Journal of Advanced Science and Technology, 2020)
Thermal image processing is an emerging technology, which has a vital role in medical and industrial applications. Application of thermal image processing helps in early detection of different diseases. Thermal image processing can be used in different industrial applications such as condition monitoring of equipments, non destructive test, building leakage identification. In this paper reviewed on thermal image capturing, thermal image processing and its industrial applications. Advancement in thermal image capturing occurred, from single element detector to thermal pixel array (TPA) of detectors.TPA detectors can capture high resolution image of smaller object from farther distance. The thermal image can be enhanced by contextual image processing technique. Image processing tools can be applied for thermal image processing such as image enhancement, image segmentation, and feature extraction. Thermal images with image processing are useful in maintenance of electrical, mechanical, and structural systems. This is a tool for detecting problems, prevent down time, guide corrective action and increase work safety.